Gray Area dan Hambatan dalam Pelaksanaan Program Pengungkapan Sukarela - Dedi Haryadi (LPPM Universitas Widya Dharma Pontianak, 2022)
The implementation of the Voluntary Disclosure Program (PPS) is regulated in the legal of Law number 7 of 2021 concerning the Harmonization of Tax Regulations. The VDP program lasts for six months from January 1, 2022 to June 30, 2022. The purpose of this study is to determine the gray areas and obstacles in implementing the voluntary disclosure program. The form of this research is descriptive research. The method of collecting data is by of a documentary study, especially on the Law on Harmonization of Tax Regulations and PMK Number 196/PMK.03/2021 and other tax regulations. The results show that there are still many gray areas and problems in the implementation of VDP, including Uncertainty for non-TA participants to disclose being a participant in Policy II so that they can disclose assets in 2015 and below, Uncertainty in net assets that must be disclosed by taxpayers who have not reported their 2020 SPT to be able to follow the policy. II, Uncertainty of Undistributed Inheritance as a participant of policy II, Disclosure of foreign assets outside the regulated KMK exchange rate is not accommodated, Uncertainty in the use of SBN/EBT investment rates for non-cash/bank assets, Uncertainty on clarification limits in policy II, Uncertainty in reporting assets originating from VDP assets, Dispute disclosure of assets in the form of savings/deposits for participants in policy I and policy II and significant tariff differences that have the potential to cause debate between taxpayers and tax authorities. The author also wants to provide suggestions in the form of the need to provide legal certainty regarding policy I only for TA participant taxpayers and revise the answers in the FAQ, certainty of the status of taxpayers with WBT status, certainty of using investment rates for assets other than cash/banks, certainty of clarification limits on policy II , technical certainty of the procedures for reporting assets in the annual SPT sourced from VDP assets and revising the VDP form so that it is able to accommodate disclosure of assets in the form of foreign currency other than the 25 types of foreign currency available.Keywords: vountary disclosure program, gray area.